Improving Storage Organization Through 5S Practices in a Welding Workshop - ABD HALIM, NURUL NABILAH; JAMIAN, RAHIM (Progress in Engineering Application and Technology, 2025)
University storage spaces are crucial for keeping tools and materials safe, organized, and easily accessible, especially in workshops where efficiency and safety are essential. However, challenges such as tool misplacement and disorganized workspace often hinder operational efficiency. This study explores the potential of 5S practices (Sort, Set in order, Shine, Standardize, and Sustain) to optimize storage organization in a welding workshop at Universiti Tun Hussein Onn Malaysia (UTHM). The research study aims to enhance storage organization and tool retrieval accessibility through the implementation of 5S practices. Additionally, the study involved designing a conceptual model for a welding tools storage organizer based on 5S principles. Genba observations in the workshop storeroom and structured interviews with users served as primary data collection methods, while descriptive analysis employed for data analysis. This study successfully delivered a practical implementation of 5S practices and a systematic design solution to enhance storage organization and tool retrieval accessibility in the welding workshop environment.